The Alzheimer's project : momentum in science - Hoffman, John, 1959-; Froemke, Susan; Golant, Susan K. (New York : BBS/Public Affairs, 2009)
Documents recent breakthroughs in Alzheimer's research, examines what the disease looks like in the human brain, and looks at specific drugs that may help.
How the brain changes: Understanding plaques ; Untangling tau ; Diagnosing early memory loss -- Advances in imaging techniques: Visualizing plaques in the living brain ; Applying new technologies in research -- The search for disease pathways: Discovering the genetics of Alzheimer's disease ; Linking Alzheimer's disease and vascular disease ; Associating Alzheimer's disease with insulin resistance and diabetes ; Learning about the role of inflammation -- Changing the outlook: Building cognitive reserve ; Assessing the potential benefits of exercise and diet ; Developing new drug treatments.
"Based on the HBO documentary presented by HBO Documentary Films and the National Institute on Aging of the National Institutes of Health in association with the Alzheimer's Association, Fidelity Charitable Gift Fund, and Geoffrey Beene Gives Back Alzheimer's Initiative."
Keywords: Alzheimer Disease; Health Education; Alzheimer's disease; Health education